Auto 365, Aesthetic Blue Wave and X50: The Steps of Diversification Strategy Implementation of Kental Bina Sdn. Bhd. - Yusof, Mohd Sufli; Kamarudin, Muhamad Ali Imran; Ramli, Azahari; Hasan, Hasnizam (2023)
Business diversification, a strategy for expanding business through new units or subsidiaries, requires careful planning. It can boost a firm’s growth, leading towards wealth maximization; however, without thorough analysis and planning, it can also lead to costly failures. This case study focuses on Kental Bina Sdn. Bhd. (KBSB) and their strategic move to diversify their business. KBSB, like many Small Medium Enterprises (SMEs), understood the need for a well-versed and clear plan to ensure business success. Their decision to diversify was the result of a comprehensive process, analyzing potential opportunities and threats in their industry as well as evaluating their own strengths and weaknesses. Understanding KBSB's diversification strategy is crucial for making informed decisions and learning from their successful expansion. Therefore, this case study provides a comprehensive understanding of the process and implications of business diversification, making it a valuable resource for businesses considering a similar path.